Assembling a Phthalocyanine and Perylenediimide Donor–Acceptor Hybrid through a Platinum(II) Diacetylide Linker. Issue 43 (13th September 2013) - Jiménez, Ángel J.; Sekita, Michael; Caballero, Esmeralda; Marcos, M. Luisa; Rodríguez‐Morgade, M. Salomé; Guldi, Dirk M.; Torres, Tomás
Abstract In a novel electron‐donor–acceptor conjugate, phthalocyanine (Pc) and perylenediimide (PDI) are connected through a trans‐platinum(II) diacetylide linker to yield Pc‐Pt‐PDI 1. In the ground state, the presence of PtII disrupts the electronic communication between the two electroactive components, as revealed by UV/Vis spectroscopy and electrochemical studies. The photophysical behavior of 1 is compared with that of the corresponding Pc‐PDI electron‐donor–acceptor conjugate 2 in terms of charge separation and charge recombination. The insertion of PtII between Pc and PDI impacts the results in a longer‐lived Pc.+/PDI.− radical ion‐pair state. In addition, the intermediately formed Pc triplet excited state is formed with higher quantum yields in 1 than in 2.